Concordance of Genomic Profiles in Matched Tissue and Plasma Samples From Chinese Patients With Lung Cancer. (October 2022) - He, Yueming; Guo, Weifeng; Xu, Meng; Huang, Junling; Zhang, Xiange; Su, Huanzhang; Hong, Dongxia; Liu, Qun
Background: Next-generation sequencing (NGS) has been widely used to identify targetable variants for patients with solid tumors, especially lung cancer. Circulating tumor DNA (ctDNA) has emerged as an alternative approach for tumor biopsy. However, the feasibility of ctDNA in detecting molecular variants remains debatable. Methods: Herein, we performed NGS on matched tissue and plasma samples from 146 Chinese patients with lung cancer. The concordance of variants between tissue and plasma samples was explored at patient and variant levels. Results: More than 80% of patients harbored at least one concordant variant in tissue and plasma samples. A total of 506 variants were shared between tissue and plasma samples, and 432 variants were identified in tissue only and 92 variants were identified in plasma only. The sensitivity and positive predictive value (PPV) of all variants detected in plasma were 53.9% and 84.6%, respectively. High concordance was observed in several driver genes. In details, epidermal growth factor receptor exon 19 deletion ( EGFR 19del), EGFR p.S768I, anaplastic lymphoma kinase ( ALK ) fusion, rearranged during transfection ( RET ) fusion, and kirsten rat sarcoma viral oncogene homolog ( KRAS ) p.G12C achieved a sensitivity of 90%, 100%, 85.7%, 100%, and 85.7%, respectively. Four EGFR -altered lung adenocarcinoma patients who underwent ctDNA-based NGS at initial diagnosis benefited from first-line gefitinib/icotinib with a median progression-free survival of 379.5 days. Conclusions: Our work provided the clinical evidence of feasibility of ctDNA-based NGS in guiding decision-making in treatment. ctDNA-based NGA could be a reliable alternative approach for tissue biopsy in patients with lung cancer.